Alismanoid A, an unprecedented 1, 2-seco bisabolene from Alisma orientale, and its protective activity against H2O2-induced damage in SH-SY5Y cells. (2nd October 2017) - Yu, Zhen-Long; Peng, Yu-Lin; Wang, Chao; Cao, Fei; Huo, Xiao-Kui; Tian, Xiang-Ge; Feng, Lei; Ning, Jing; Zhang, Bao-Jing; Sun, Cheng-Peng; Ma, Xiao-Chi
Abstract : A pair of unprecedented 1, 2- seco bisabolenes, (8 R )-alismanoid A (1a ) and (8 S )-alismanoid A (1b ), were isolated from A. orientale . Abstract : A pair of novel sesquiterpenoids, (8 R )-alismanoid A (1a ) and (8 S )-alismanoid A (1b ), possessing an unprecedented 1, 2- seco bisabolene carbon skeleton, were isolated from rhizomes of Alisma orientale together with two new sesquiterpenoids: a 15- nor guaiane alismanoid B (2 ) and alismanoid C (3 ). Their structures were elucidated by 1D and 2D NMR, HRESIMS, electronic circular dichroism (ECD), and theoretical calculations, and a plausible biosynthetic pathway for compound1 is discussed. Meanwhile, compounds1–3 were investigated for their protective effects on H2 O2 -induced damage in human dopaminergic neuroblastoma cells (SH-SY5Y), and compounds1b, 2, and3 showed significantly protective activities at a certain concentration. Further, the action mechanism of compound3 was proved to be through inhibition of H2 O2 -induced apoptosis in SH-SY5Y cells. Herein, these results suggest that sesquiterpenoids are potential candidate drugs for treating Parkinson's disease induced by reactive oxygen species.